Teknologi Informasi Dan Komunikasi (TIK) Untuk Guru Matematika Tingkat SMA Di Kabupaten Enrekang (Information and Communication Technology (ICT) for Mathematics Teachers of Senior High School In Enrekang Regency) - Mahie, Andi Galsan; Amir, Amir Kamal; Firman, Firman; Massalesse, Jusmawati; Aris, Naimah; Anisa, Anisa (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2018)
Mathematics Study Program, Department of Mathematics FMIPA UNHAS as the State Higher Education Institution makes a Community Service activity as a form of caring for the environment, especially in improving Human Resources (HR) for high school teachers in mathematics studies in Enrekang Regency. The Regional Science and Technology Community Service Program (IbW) is one solution for the problem. This IbW program is a series of activities of Hasanuddin University's 62nd Anniversary which has been carried out in the Hall of SMA 1 Enrekang 1 in Anggeraja District, Enrekang Regency. The partners involved were 14 schools at the SMA/SMK/MAN level in Enrekang Regency with a total participants is a varied school with a total of 40 teachers. The purpose of this Community Service implementation was to SMA Mathematics Teachers in Enrekang Regency to increase their passion to teach them to be more varied focused on visualization so that mathematics looks more real. Some science and technology packages that have been implemented are: 1). Microsoft Excel software, 2). Maple software and 3). Geogebra Software. The results of this activity can improve the competence of mathematics teachers in the enrichment of subjects to their students.